Global Voices in Higher Education - Renes, Susan L. (IntechOpen, 2017)
Traveling from Zimbabwe to New Zealand and on to Ghana and the United States, the voices of higher education are presented in a way only scholars from these regions can fully articulate and understand. The changing world of higher education challenges all of those involved in very unique ways. In Global Voices in Higher Education, scholars from 10 different countries share their work, describing not only their research but also the context in which their work exists. This book allows the reader to travel with these scholars to their colleges and universities and discover areas of concern in higher education from around the globe.